Russia's role in the contemporary international agri-food trade system - Wegren, Stephen K., 1956-; Nilssen, Frode (Palgrave Macmillan, 2022)
This Open Access book analyses the emergence of Russia as a global food power and what it means for global food trade. Russia's strategy for food production and trade has changed significantly since the end of the Soviet period, and this is the first book to take account of Russia's rise as a food power and the global implications of that rise. It includes food trade policy and practice, and developments in regional food trade. This book will be of interest to academics and practitioners in agricultural economics, international trade, and international food trade. Stephen K. Wegren is Distinguished University Professor, Professor of Political Science at Southern Methodist University, USA, and Director of International and Area Studies, Southern Methodist University. Frode Nilssen is Professor at Nord University Business School, Norway, and the Head of Department for Marketing, Strategy and Management at Nord University Business School.
Includes index.
Keywords: Produce trade -- Russia (Federation); Agriculture -- Economic aspects -- Russia (Federation); Produits agricoles -- Commerce -- Russie.; Agriculture -- Aspect économique -- Russie.; Agriculture -- Economic aspects; Produce trade; Russia (Federation)